BACTERIOLOGICAL HAZARDS AND RISKS ASSOCIATED WITH SEAFOOD CONSUMPTION IN BRAZIL - Santos, Carlos A.M. Lima dos; Vieira, Regine H. S. Fernandes (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
SUMMARY The present study is a review of data available in Brazil on bacterial diseases transmitted through the consumption of seafood and related products. Data are presented regarding outbreaks and cases of disease and laboratory findings associated with pathogens in seafood and related products, and methods for prevention and control are described.